Values as Vessels of Religion? - Harald Askeland; Gry Espedal; Stephen Sirris (Diaconia, 2019)
This paper investigates if and how religion is translated through values in everyday work in three Norwegian faith-based healthcare organizations (FBHOs). It provides insights into how values translate religion in the organizational self-representations of FBHOs and the symbolic practices of executives. Further, we analyze the use of values in organizational policy documents and the role of values as a common ground for framing and interpreting organizational and professional practices. We discuss the contributions of values toward maintaining religious traditions. This study identifies ways in which values translate and express the presence of religion while highlighting the shortcomings of their potential role in mediating religion.